(untitled) (Journal of the College of Basic Education, 2022)
All societies depended on what their people have of prosperities. In order in establish the main bases, as well as the affective facilities and the fruitful efforts through different horizons of life within a scientific and subjective frame.During the scientific progress in all centuries Testing Batteries had been considered as one of the major mean that helped to develop and serve humanity generally form one hand as well as studies and researcher from the other one. The problem of the research is how to make a Testing Battery for students who are to be accepted in the Department of Art Education college of Fine Arts / Baghdad University. The aim of this research is: To establish a Testing Battery for students who are supposed to be submitted in the Department of Art Education / college of Fine Arts / Baghdad University. Beside to measure its validity upon an average of student who are already accepted in the Department of Art Education for Art Education for the years 2007/2008.Upon this light, the researcher prepared a Testing Battery on asperies of students under the conditions and bases to build the Testing on About (55) students who were accepted in the first class of the year 2007/2008 to check the validity of this Battery. This Battery consists of five separate cells. Each of which in itself four different Testings and they are: the knowledge testing, the Plastic (practical) Testing, the Acting Performance Testing and the Personality Testing. These four testing are considered according to the classifications form which the curriculum of the department that is known as a varictical one in its curriculums since it is responsible for the graduating students who are supposed to be scientifically and artistically qualified to be teachers in the future within the secondary education in Iraq . The data has been processed statistically by using two different coefficients, Discrimination coefficient and kuder Richardson’s coefficient / 20. So that to find out the reability and CrounBach – Alfa Equation so that calculate harmonial coefficient (reability) and to see the arrangement (reability). This operation is done by using Holesty’s Equation in the plastic (practical). Testing as well as the agreement coefficient for Acting performance Testing.The result ’s of this research comes out like that , the success of this Battery after its application, that is why the researcher recomends these who might be concerned to get use from the Testing Battery in order to limit the level of students who are to be accepted within this Battery’s terms and conditions . The researcher also recommends to do studies for designing and making Testing Batteries in the colleges and institutions of Fine and Applied Arts, as well as in the institutions of teachers in Iraq.